2012
DOI: 10.1002/iub.1089
|View full text |Cite
|
Sign up to set email alerts
|

FHL family members suppress vascular endothelial growth factor expression through blockade of dimerization of HIF1α and HIF1β

Abstract: SummaryFour and a half LIM domain (FHL) proteins belong to a family of LIM-only proteins that have been implicated in the development and progression of various types of cancers. However, the role of FHL proteins in tumor angiogenesis remains to be elucidated. Herein, we demonstrate that FHL1-3 decrease the promoter activity and expression of vascular endothelial growth factor (VEGF), the key regulator of angiogenesis in cancer growth and progression as well as an important target gene of the transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Moreover, reciprocal coimmunoprecipitation experiments showed that GATA1, SET7, Pol II, and TFIIB interacted with each other (Figure 4H ). GATA1 did not interact with HIF1α although HIF1α interacted with four and a half LIM protein 1 (FHL1) as we previously reported [ 49 ] ( Supplementary Figure S7C ). Taken together, these results suggest that GATA1, SET7, Pol II, and TFIIB may form a preinitiation complex on the GATC site of VEGF promoter.…”
Section: Resultssupporting
confidence: 69%
“…Moreover, reciprocal coimmunoprecipitation experiments showed that GATA1, SET7, Pol II, and TFIIB interacted with each other (Figure 4H ). GATA1 did not interact with HIF1α although HIF1α interacted with four and a half LIM protein 1 (FHL1) as we previously reported [ 49 ] ( Supplementary Figure S7C ). Taken together, these results suggest that GATA1, SET7, Pol II, and TFIIB may form a preinitiation complex on the GATC site of VEGF promoter.…”
Section: Resultssupporting
confidence: 69%
“…Since STAT3 and ARNT modulate HGF, VEGF and G-CSF expression a (Albasanz-Puig et al, 2012, Lin et al, 2012, Tacchini et al, 2003, Nguyen-Khac et al, 2006, Zhang et al, 2012, Zimmers et al, 2003), we analyzed HGF and VEGF levels by western blot in lysates of PBMC transfected with miRNA 181/221 and mimics or antagomirs and then stimulated with PMA/ionomycin (Fig 7D–F). Secretion of G-CSF into culture supernatant was carried using singleplex assay because we were not able to detect protein expression using the commercially available antibody (Fig 7G).…”
Section: Resultsmentioning
confidence: 99%
“…As STAT3 and ARNT modulate HGF, VEGF, and G-CSF expression (Albasanz-Puig et al, 2012;Lin et al, 2012; -Khac et al, 2006;Tacchini et al, 2003;Zhang et al, 2012;Zimmers et al, 2003), we analyzed HGF and VEGF levels by Western blot in lysates of PBMC transfected with miRNA 181/221 and mimics or antagomirs and then stimulated with PMA/ionomycin ( Fig. 7D-F).…”
Section: Mir-181 and Mir-221 Modulate Stat3 Arnt Hgf Vegf And G-cmentioning
confidence: 99%
“…Nadeau et al ( 27 ) observed that vascular endothelial growth factor (VEGF) was upregulated in a neonatal pig model of HPH. In human HepG2 hepatoma cells, FHL1 decreased the expression and activity of VEGF by blocking the dimerization of HIF-1α and HIF-1β ( 28 ). Thus, FHL1 may have exerted similar effect in the current HPH neonatal rat model.…”
Section: Discussionmentioning
confidence: 99%